PENINGKATAN PELAYANAN KEPADA MASYARAKAT DENGAN LITERASI DIGITAL KELURAHAN BERBASIS TEKNOLOGI INFORMASI - Hendri, Halifia; Robianto, Riska; Salim, Emil (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
One of the subdistricts in West Padang District, Padang City, West Sumatra Province, is Kampung Pondok Subdistrict. This sub-district has an area of approximately 1 km2 and a population of approximately 3,539 people, divided into 1740 men and 1799 women. Even though this sub-district consists of 11 Rukun Warga (RW), community members tend to visit the Lurah Office directly (offline) to get information and take care of everything. This community service is important and interesting for the Kampung Pondok Village officials. This activity gave them a new understanding of the importance of using the subdistrict website to disseminate information, news, and announcements quickly, precisely, and accurately. There are two problems in the place where PKM activities are carried out, namely first that they do not have media that can be used to disseminate digital information to the community and second that there are no services that can be provided to the community online. This PKM activity aims to enable sub-district officers and the surrounding community to easily disseminate data, services, and information online via the sub-district website. The mentoring and training techniques applied in this PKM aim to facilitate the activities of sub-district officials consisting of 30 people. After the PKM is completed, the evaluation process begins. The evaluation carried out was to measure the level of satisfaction, level of existence, and level of user satisfaction using a questionnaire. The results obtained were that the satisfaction level of activity participants was 75%, the level of benefit from having a website for sub-district officials was 80%, and the level of ability to use the website for sub-district officials was 73%.